The Impact of Low-Code and No-Code Development on IT Workforces and Software Engineering Practices in Indonesia - Jasman, Jasman (West Science Information System and Technology, 2024)
This study examines the impact of low-code and no-code (LCNC) development platforms on IT workforces and software engineering practices in Indonesia. Employing a quantitative approach with 50 respondents and data analysis using SPSS version 25, the research investigates the relationships between LCNC adoption and variables such as workforce productivity, skill adaptability, software quality, and development efficiency. The findings indicate that LCNC platforms significantly enhance workforce productivity and development efficiency, with moderate impacts on skill adaptability and mixed perceptions of software quality. These results suggest that LCNC platforms have the potential to revolutionize software development processes in Indonesia, provided that challenges related to skill adaptation and quality assurance are effectively addressed.